2020
DOI: 10.1177/1542316620918555
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Food Security Through Localisation, Not Aid: “De-development” and Food Sovereignty in the Palestinian Territories

Abstract: Food aid is a common response to the food insecurity brought by conflict and inadequate development. Yet the very well-intentioned actions that are meant to stave off immediate humanitarian crises may, in the long-term, serve as tools that promote dependence, decrease the likelihood of sustainable development, and make peace less possible. In this article, I examine food insecurity and food aid in the conflict-affected Palestinian territories. I will describe ways in which Palestinian efforts to localise food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…It can also be noted that "Zero Hunger" in Gaza Strip had Beta of 0.436, which is higher than that of Hungary, which scored Beta of 0.377, and that is due to the high poverty rates in the Gaza Strip and the absence of the required funding to support the hunger and poverty programs to alleviate both poverty and hunger, as for Hungary it has specific programs to alleviate poverty and ensure food security for its citizens and the findings of this research complies with the findings of Asi (2020).…”
Section: Comparison Between Gaza Strip and Hungarysupporting
confidence: 71%
See 1 more Smart Citation
“…It can also be noted that "Zero Hunger" in Gaza Strip had Beta of 0.436, which is higher than that of Hungary, which scored Beta of 0.377, and that is due to the high poverty rates in the Gaza Strip and the absence of the required funding to support the hunger and poverty programs to alleviate both poverty and hunger, as for Hungary it has specific programs to alleviate poverty and ensure food security for its citizens and the findings of this research complies with the findings of Asi (2020).…”
Section: Comparison Between Gaza Strip and Hungarysupporting
confidence: 71%
“…While Palestinian herders are only allowed access to 31% of Palestinian rangeland, Palestinian fishermen have only been allowed access to 35% of the area allocated to them under the Oslo Accords in Gaza, a coastal zone with 35,000 fishermen (6 out of 20 nautical miles). In April 2016, when Israel raised the permissible sea access in certain areas to nine nautical miles, the amount of fish captured surged more than fivefold, according to Asi (2020). Since the conflict in 2014, four fish farms have been constructed in Gaza to help locals get around fishing bans.…”
Section: Resource Accessmentioning
confidence: 99%
“…In another study, researchers found that the more cultural factors are present in Indigenous life, including the pursuit of land claims to counter settler colonial dispossession, the lower the risk of suicide among Native youth ( 196 ). Across settler state contexts from Oceania to the Americas and in between, food sovereignty among Māori, First Nations, Palestinian, and other Indigenous communities is a growing area of interest in defying the ongoing impacts of settler colonialism ( 1 , 197 , 198 ), and Indigenous scholars continue to push for collective approaches to resilience and resistance rather than the individualistic focus of settler discourse at state and academic levels ( 199 ). Finally, challenges to Indigenous data genocide are increasingly mounted, including through the settler colonial reframing and reevaluation of prior studies.…”
Section: Argumentmentioning
confidence: 99%
“…This long-simmering interdependence of war and the agro-economy erupts clearly in the U.S.'s recently authorized US$14 billion in military aid to Israel (atop the US$3.8 billion in yearly arms aid) while that allied settler state metes out the collective punishment of Palestinians, monumental bombardment, chemical warfare, and genocidal deprivation of food, water, medicine, fuel, internet, or egress from the "open air prison" of Gaza. This onslaught erupts atop decades of "slow violence" (Amira, 2021) of Israeli settler destruction of Indig-enous Palestinian agricultures (Abdelnour et al, 2012) and systemic dispossession of their sea, fisheries, water, lands, orchards, olive groves (Asi, 2020, Sasa 2023, and seeds (Sansour, 2022). Beyond "security" apartheid walls rimmed with barbed wire, surveillance, and AI weaponry, what food and health systems would be made possible were those billions of dollars invested otherwise?…”
mentioning
confidence: 99%